Isolation, identification, and characteristics of local yeast isolates with proteolytic capability obtained from traditional processed Indonesian duck eggs - Pratama, Andry; Gumilar, Jajang; Putranto, Wendry S.; Rukayadi, Yaya (Journal of Pure and Applied Microbiology, 2024)
Various microorganisms can grow in egg-based food products, and yeast is among the microorganisms that thrive in egg products. Yeasts naturally produce large enzymes by breaking down organic materials during growth. Yeast has a great biotechnological potential owing to its extracellular enzymatic activity. Therefore, it is important to study yeast species, especially those from food sources and the environment. Protease production and activity are affected by various factors such as temperature, time, and pH. In this study, 47 yeast isolates were identified and purified from traditionally processed Indonesian duck eggs via repeated sub-culturing and quadrant streaking. Screening of the yeast isolates on skim milk agar medium showed that 23 isolates exerted proteolytic activity, whereas the remaining 25 did not. Yeast isolates with proteolytic capabilities belonged to the Saccharomyces, Pichia, and Candida genera. The highest protease activities were observed in isolates TA-17 and TPi-08, with activity values of 0.618 and 0.098 U/mL, respectively.